HYDROCARBONS IN THE NORTHERN BARENTS SEA - Nemirovskaya I.A. (My University, 2001)
Data are presented on the content and composition of aliphatic and polycyclic aromatic hydrocarbons (HCs) in snow, ice core, water, and bottom sediments from the northern Barents Sea, within the FranzVictoria trough. It was established that, in spite of the comparatively high hydrocarbon concentrations in snow, ice core, and in the water column of the density gradient layer, their distribution is mainly controlled by natural hydrobiological and geochemical conditions, and natural factors define the main regularities of their migration; only fresh snow demonstrates the contribution of pyrogenic sources.